Antecedents and consequences of self-congruity - Roy, Rajat; Rabbanee, Fazlul (Emerald, 2015)
Purpose– This study aims to propose and test a parsimonious framework for self-congruity, albeit in the context of luxury branding. This paper is the first to propose an integrated model focusing on the drivers and consequences of self-congruity. The model is further applied to explain how self-congruity may motivate future experiences with the luxury brand, mainly by influencing self-perception. Although a substantive marketing literature on self-congruity currently exists, there is a lack of an integrated framework, a gap that the current work addresses. Design/methodology/approach– A paper and pencil survey was conducted among female subjects only, and structural path relationships were tested using AMOS. Findings– Consumers’ self-congruity with a luxury brand (non-luxury brand) is positively (negatively) influenced by its antecedents: social desirability, need for uniqueness and status consumption. Self-congruity with a luxury (non-luxury) brand is found to enhance (undermine) consumers’ self-perceptions. This, in turn, is found to have a stronger (weaker) positive impact on consumers’ motivation to re-use a shopping bag from luxury brand (non-luxury brand) for hedonic purpose. Mediation analyses show that self-congruity has a positive (negative) indirect effect on hedonic use via self-perception for luxury (non-luxury) brand.Research limitations/implications– Future studies may involve actual shoppers, causal design and additional variables like “utilitarian usage “of shopping bags to extend the proposed framework. Practical implications– A better understanding of the findings has implications for brand positioning, advertising and packaging. Originality/value– Till date, no research has examined a parsimonious model for self-congruity complete with its antecedents and consequences and tested it in the context of a luxury versus non-luxury brand.